Study on the Influence of Perforation Parameters on the Initiation Pressure of Hard Rock - SHI Yao; SHENG Tingqiang; LI Bihong; ZHU Xiuxing; LI Chao; JIE Zhijun (Cejing jishu)
The middle and deep layer of BZ gas field are mainly hard rocks, and the reservoir fracturing pressure is high, which increases the difficulty and risk of fracturing operation. Perforating channel is the passageway to transmit fracturing power, thus optimizing perforating parameters is an important measure to reduce rock fracture pressure. Based on the theory of fracture phase field and the coupling equation of fracturing fluid flow and rock stress damage, fracture extending model based on phase field method is established, and the reliability of the model is verified by field data. Combined with the rock mechanics interpretation data of BZ gas field and the shooting test of perforating charge, fracturing software is used to simulate the variation law of hard rock fracturing pressure under different perforation schemes. When the perforation is in the direction of the maximum horizontal principal stress, the rock initiation pressure is the smallest. In spiral perforation, when the phase gets larger, the hole density and the maximum fracturing pressure are getting smaller. The influence of pore diameter on the initiation pressure is small without considering the influence of pore friction. With the increase of penetration depth, the crack initiation pressure decreases, and when the penetration depth is less than 100 mm, the decrease is large. It is recommended to adopt directional perforation in BZ gas field. The perforation direction is along the direction of maximum principal stress, the perforation density is greater than 16 holes/m, the perforation depth is greater than 100 mm, and the aperture is as large as possible. If spiral perforation is used, the perforation phase is less than 60°. The research results provide a reference for the optimization of perforation parameters of hard rock in BZ gas field.